The Use of High Resolution Melting (HRM) Method to Detect rs1800629 of Tumor Necrosis Factor-alpha (TNF-alpha) Gene among Tuberculosis Patients - Kinasih Prayuni; Intan Razari; Silviatun Nihayah; Rika Yuliwulandari (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2021)
The rs1800629 polymorphism plays a crucial role in the pathogenesis of infectious and autoimmune diseases. Meanwhile, tuberculosis (TB) remains a health primary infectious disease in Indonesia. The purpose of this study is to evaluate the HRM method in detecting the rs1800629 genotype, in the TNF-α gene’s promoter region, within TB patients. The benefit of this study is to accelerate the detection of rs1800629 with a simple, rapid, and cost-effective method for genotyping and mutation screening that does not include the use of a fluorescent probe. In this experimental study, the rs1800629 genotyped in a total of 25 tuberculosis patients using KAPA HRM kit in MyGo Mini PCR, and all amplified PCR products subsequently dispatched for direct DNA sequencing to Macrogen Inc, South Korea. Based on the results, a 100% concordance find in the genotyping of rs1800629 between HRM and sequencing. The authors provided evidence to use HRM in detecting rs1800629 within the TNF-α promotor region. This application as a genotyping assay in tuberculosis patients is a low-cost, rapid, and accurate detection. However, further studies using the HRM method in case-control samples of tuberculosis are required to evaluate the method’s effectiveness and to obtain more information regarding the genotype’s susceptibility to tuberculosis and its adverse effect treatment, including anti-tuberculosis drug, induced liver injury (AT-DILI), and multidrug-resistant TB (MDR-TB), within the Indonesian population.